UNGKAPAN RASA TERKEJUT DALAM RAGAM KANYOUKU - Yuliani Rahmah (IZUMI, 2014)
This paper describes about Kanyouku which used in Japanesse daily conversation. Kanyouku used to express what we feel about something more specific than the common sentences. There are many expressions of kanyouku, but this paper  is focused on a kanyouku which used to show surprise expressions. Kanyouku that introduced in this description only 10 of Doushi Kanyouku types. Those kanyouku  not only described the meanings but  also given examples of simple sentences that are commonly encountered in daily conversation.